El civil law frente al precedente judicial vinculante: diálogos con académicos de América Latina y Europa - Castro, Jordi Delgado (2021)
This paper addresses binding judicial precedent. The semi- structured interview was used as a methodology for execution and a total of thirty-two academics, from ten countries in Latin America and Europe, participated of it. The results are structured around the arguments for and against precedent as a theoretical position; to narrate how vertex courts and inferior courts behave on precedents; and finally, to know the roadblocks that prevent following precedent correctly.